The influence of different lipid environments on the structure and function of the hepatitis C virus p7 ion channel protein - Whitfield, T; Miles, A; Scheinost, J; Offer, J; Wentworth, P; Dwek, R; Wallace, B; Biggin, P; Zitzmann, N (Taylor and Francis, 2011)
The hepatitis C virus (HCV) encodes the p7 protein that oligomerizes to form an ion channel. The 63 amino acid long p7 monomer is an integral membrane protein predominantly found in the endoplasmic reticulum (ER). Although it is currently unknown whether p7 is incorporated into secreted virions, its presence is crucial for the release of infectious virus. The molecular and biophysical mechanism employed by the p7 ion channel is largely unknown, but in vivo it is likely to be embedded in membranes undergoing changes in lipid composition. In this study we analyze the influence of the lipid environment on p7 ion channel structure and function using electrophysiology and synchrotron radiation circular dichroism (SRCD) spectroscopy. We incorporated chemically synthesized p7 polypeptides into artificial planar membranes of various lipid compositions. A lipid bilayer composition comprising phosphatidylcholine (PC) and phosphatidylethanolamine (PE) (4:1 PC:PE) led to burst-like patterns in the channel recordings with channel openings lasting up to 0.5 s. The reverse ratio of PC:PE (1:4) gave rise to individual channels continuously opening for up to 8 s. SRCD spectroscopy of p7 embedded into liposomes of corresponding lipid compositions suggests there is a structural effect of the lipid composition on the p7 protein.